Evaluation of the Addition of Eugenol of Clove Leave Essential Oil in the Ration on Phenol and Antioxidant Levels of Male Laying Hens Meat - Muhammad Tahir; Hafsah Hafsah; Andi P. Damayanti; Rizal Y. Tantu (Jurnal Akademika Kimia, 2022)
Eugenol is a component of phenol, biologically it can function as an anti-bacterial, anti-fungal, insecticide, and antioxidant. The content of eugenol which is quite large in clove leaf essential oil is used as a bioactive substance to increase antioxidant levels in meat. Experimental by using 100 male laying hens were then placed into 20 cage units, each cage unit filled with 5 experimental chickens. Meat sample collection for analysis of phenol and IC50 levels was carried out by slaughtering experimental chickens at 8 weeks of age. Samples of chicken meat were taken from the breast of each experimental animal as much as 100 grams. Determination of the total phenol content of chicken meat using Folin-Ciocalteu with gallic acid as a comparison, while the antioxidant activity testing using the DPPH free radical absorption method. In this experiment, eugenol was added to the basal ration with 5 treatments, namely: E0 = without eugenol; E1 = 0.5% eugenol; E2 = 1% eugenol; E3 = 1.5% eugenol; E4 = 2% eugenol.  The variables observed were phenol levels and IC50 values which can describe the antioxidant power in male laying hens. The results showed that the addition of clove leaf eugenol as an additive in the ratio had a very significant effect (p < 0.01) on phenol levels and IC50 values. male laying hens. Each increase in the use of 0.5% eugenol in the ration can increase the phenol content and decrease the IC50 value significantly in the meat produced. The level of eugenol in the ration was positively correlated with the levels of phenol and antioxidants in the meat of laying hens, while the levels of eugenol in the ration and the levels of phenol in the meat had a negative correlation with the IC50 value of the meat of laying hens.